In the non-historical reading of the thought of Mohammed Abed AlJabri - Al-Saleh, Iman (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
In his book, Al-Jabri offers a profound account of the issue of Arab modernity by revisiting the Arab heritage and revealing its sources, criticizing the obstacles that hinder Arab societies and realizing their modernity, i.e. the revolution that allows to overcome delays and Salafism, and then rise to the logic of the times to protect interests and secure self-defense against The ambitions of the other. The problem with which alJabri is based is: How can we restore the glory of our civilization? How to salute our heritage? And how to live our time? How do we deal with our heritage? And how to achieve our revolution? How to rebuild our heritage? These are questions that Jabri provided analyzes and answers from his perspective, in anticipation of an Arab revolution, it is an in-depth diagnosis of erroneous Arab modernity, and the conclusion of the vast divergence between the usual curricula in his study of heritage, Ready solutions for present and future problems. If this applies quite clearly to the religious trend, it also applies to other currents, since each of them has a predetermined recourse to it, where he believes that modern and contemporary Arab thought is, in the sentence, an historical one that lacks a minimum of objectivity. Therefore, his reading of heritage was a Salafist reading that preaches and sanctifies the past and derives from it ready solutions for the problems of the present and the future. If this applies quite clearly to the religious trend, it also applies to other currents, since each of them has a predetermined leaning on it and invokes it. يُقدّم الجابري في كتاباته طرحاً عميقاً لمسألة الحداثة العربية من خلال إعادة النظر في التراث العربي والكشف عن مصادره، وانتقاد العوائق التي تحول بين المجتمعات العربية وتحقيق حداثتها، أي الثورة المتيحة لتجاوز التأخر والسلفية، ومن ثم الارتقاء إلى منطق العصر لحماية المصالح وتأمين الدفاع عن النفس ضد أطماع "الأخر". إن الإشكالية التي ينطلق منها الجابري هي: كيف نستعيد مجد حضارتنا؟ كيف نحيي تراثنا؟ وكيف نعيش عصرنا؟ كيف نتعامل مع تراثنا؟ وكيف نحقق ثورتنا؟ كيف نعيد بناء تراثنا؟ وهي أسئلة قدم لها الجابري تحليلات وأجوبة من منظوره هو، استشرافاً لثورة عربية، هي في العمق تشخيص ضمني للحداثة العربية المخطئة، وإبراز للتباعد الشاسع بين المناهج المعتدة في دراسته التراث، حيث يرى أن الفكر العربي الحديث والمعاصر هو في الجملة فكر لا تاريخي يفتقد إلى الحد الأدنى من الموضوعية، ولذلك كانت قراءته للتراث قراءة سلفية تنزه الماضي وتقدسه وتستمد منه الحلول الجاهزة لمشاكل الحاضر والمستقبل. وإذا كان هذا ينطبق بوضوح كامل على التيار الديني, فهو ينطبق أيضاً على التيارات الأخرى باعتبار أن لكل منها سلفاً يتكئ عليه ويستنجد به.